Therapeutic drug monitoring of osimertinib in non-small cell lung cancer and short bowel syndrome: a case report - Longuespée, Rémi; Kunz, Julia; Fresnais, Margaux; Foerster, Kathrin; Burhenne, Jürgen; Thomas, Michael; Kazdal, Daniel; Stenzinger, Albrecht; Christopoulos, Petros; Haefeli, Walter E. (British journal of clinical pharmacology, 2024)
Short bowel syndrome (SBS) following extensive intestinal resection is often characterized by impaired absorption of orally administered drugs, including tyrosine kinase inhibitors (TKI). We report the case of a patient with EGFR-mutated non-small cell lung carcinoma treated with 80 mg/day of the TKI osimertinib who achieved partial response of the tumour, but was subsequently subjected to a double-barrelled jejunostomy due to ileus. Due to the development of SBS after the bypass surgery, plasma concentrations of osimertinib were monitored using mass spectrometry. The therapeutic drug monitoring confirmed a malabsorption of osimertinib in the patient (108 ng/mL, which is below the 5th percentile of the expected plasma concentration) and was useful to guide adjustments of TKI dosing in order to achieve adequate blood levels (161 ng/mL after increase of the dose to 120 mg/day) in order to maintain tumour control.
Erstveröffentlichung: 10. Oktober 2023
Gesehen am 06.02.2024